Liberty and Democracy in Tocqueville: A Contrast Between the Spontaneous Decentralization of American Democracy and the Rationalized Centralization of the French Revolution - Paz, Anderson (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
The purpose of this article is to identify, in Alexis de Tocqueville’s reading, the contrast between the spontaneous decentralization of American democracy and the rationalist centralization of the French Revolution. From reading Tocqueville, we will analyze the hypothesis that the particularity of the empiricist and customary tradition of the United States prevented it from suffering the consequences of a centralizing republic model born in the French Revolution, based on the continental rationalist tradition. The approach of this work is qualitative, and the methodology is exploratory through a bibliographic review of Tocqueville’s two main works, Democracy in America (1835 and 1840) and The Old Regime and the Revolution (1856). In Tocqueville’s reading, we conclude that there is a contrast between the spontaneous decentralization of American democracy that seeks to reconcile equality of conditions and individual freedom and the rationalist centralization of the French Revolution.